Vortex tube performance data sheets - Westley, R. (College of Aeronautics, 1957)
Experiments to determine the effect of various operating and design parameters on the performance of a vortex tube are described in College of Aeronautics Note No. 30. The present note gives additional performance data on this tube and should be used as a supplement to Note No.30. These data sheets are intended as an aid to the estimation of the performance of vortex tubes and to the design of vortex tubes with given characteristics. In particular, the present note provides the optimum values of the vortex tube parameters which give maximum temperature drops. Figures 12-53 give temperature drop and cold mass flow ratio characteristics, figures 54-61 give the cold mass flow ratios at maximum temperature drop whilst figures 62-65 give the optimum inlet and cold outlet sizes for maximum temperature drop.